2022
DOI: 10.3390/vaccines10101694
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Adjuvant System for Intranasal Boosting of Local and Systemic Immunity for Influenza Vaccination

Abstract: Systemically vaccinated individuals against COVID-19 and influenza may continue to support viral replication and shedding in the upper airways, contributing to the spread of infections. Thus, a vaccine regimen that enhances mucosal immunity in the respiratory mucosa is needed to prevent a pandemic. Intranasal/pulmonary (IN) vaccines can promote mucosal immunity by promoting IgA secretion at the infection site. Here, we demonstrate that an intramuscular (IM) priming-IN boosting regimen with an inactivated influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…administration of a synthetic DNA plasmid expressing Spike trimer with a chemokine adjuvant is effective at inducing mucosal antibodies and T cells 50 . A liposomal formulation containing TLR4 and TLR7 agonists was also shown to be an effective mucosal adjuvant for an influenza vaccine in mice 51 .…”
Section: Discussionmentioning
confidence: 99%
“…administration of a synthetic DNA plasmid expressing Spike trimer with a chemokine adjuvant is effective at inducing mucosal antibodies and T cells 50 . A liposomal formulation containing TLR4 and TLR7 agonists was also shown to be an effective mucosal adjuvant for an influenza vaccine in mice 51 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a systemic prime-intranasal boost strategy with an influenza vaccine adjuvanted with the liposomal dual TLR4/7 adjuvant has been shown to enhance both systemic and local/mucosal immunity. This regimen results in the secretion of antigen-specific sIgA and development of tissue-resident memory T cells in the respiratory tracts, as well as cross-reactive sIgA to multiple influenza virus strains ( 140 ). Similarly, this prime-boost strategy has been successful in preventing SARS-CoV-2 transmission and disease development through vaccination ( 141 ).…”
Section: Future Perspective Of Saponin-based Adjuvantsmentioning
confidence: 99%
“…The AS01 B was chosen in this study because a recent report from our group showed that AS01 B -containing vaccines can be converted to dry powders by TFF (AboulFotouh et al, 2022b). Results from a recent study have demonstrated the safety and efficacy of AS01 B as a potential nasal vaccine adjuvant in a mouse model (Sato-Kaneko et al, 2022). Moreover, one can find in the literature intranasal immunization studies wherein the vaccines contain either monophosphoryl lipid A (MPL) or QS21 as the adjuvant (Baldridge et al, 2000; Sasaki et al, 1998a; Sasaki et al, 1998b), and the liposomal AS01 B contains both MPL and QS21.…”
Section: Introductionmentioning
confidence: 99%